CREATION OF THE COMPETITION’S PROFILE OF SERBIA AS A TOURISM DESTINATION - Ubavić, Predrag D (International Journal of Economic Practice and Policy, 2015)
During the last several decades tourism has more and more significant role in economic and social development of other countries, as well as in everyday life of a contemporary man. The Republic of Serbia, also, tends to use valorization of its touristic potentials to realize numerous objectives of its economic and general social development. Number of destinations that offer their tourist products on the tourist market increases, leading to intensified competition. Competitiveness is emphasized as a crucial issue in contemporary tourism, as destinations strive to be better than competitors. Observed from today’s perspective we can come to a general conclusion that Serbia as a touristic destination, still hasn’t taken adequate competitive position regarding other tourist destinations in the region. The aim of this paper is to point out the necessity of repositioning the present competitive position of Serbia to make it, within as short time period as possible, an attractive tourist destination on the regional and international tourist market. With adequate implementation of theoretical concepts and chosen research methods this paper is expected to enrich domestic professional literature from this field, also to point out new possibilities of Serbian tourism development to creators and those who carry out such economic and touristic politics.